Business model innovation and SMEs’ resilience: technological roadmap in Nigeria - Alake, Oluwakemi R.; Adegbuyi, Omotayo; Babajide, Abiola A.; Salau, Odunayo P.; Onayemi, Oluwakemi O.; Joel, Opeyemi O.; Adesanya, Oluwatoyin D. (Business: Theory and Practice, 2024)
Business sustainability is a factor that businesses, especially SMEs, are giving more and more thought to. Businesses are now looking for methods to integrate sustainable practices into their operations while keeping their business models intact as a result. This study primarily looks at how technology might improve company resilience in order to investigate the connection between SMEs’ business models and their pursuit of sustainability. To enable the study’s main goals be achieved, three hypotheses were developed. The study’s goal was explained using the Resource Based View Theory, Dynamic Capability Theory, and Institutional Theory. By combining purposive and convenience random selection approaches, the researchers performed a field survey of 420 SME operators in Nigeria in order to meet this goal. Smart PLS 3.0 was utilized in the study to evaluate the information gathered. Specifically, they assessed the extent and strength of the correlations between these constructs using path coefficients, t-statistics, R-square values, and p-values. According to the study, technology competence moderates the association between business model innovation and businesses’ resilience, indicating that by utilizing technological skills, business model innovation’s beneficial effects on a firm’s resilience may be amplified. The technology acceptance concept, which contends that adopting new technology may enhance organizational performance, is supported by this research. As SMEs frequently deal with budget limitations and technology difficulties, the study’s findings have significant significance for them. SMEs may be better positioned to survive upheavals and develop resilience by adopting new business strategies and utilizing technical skills. The study discovered that in order to increase their resilience, SMEs must actively adapt to fast-paced and competitive environments using their internal strengths. This indicates that SMEs must assess the value of innovation models in relation to their specific line of business. The study emphasizes the significance of the network interaction between technological innovation, business model innovation, and SMEs’ resilience. The capacity to use technology, which is essential for boosting SMEs’ resilience, strengthens this link. In summary, this study offers a current road map for technical development in the context of novel business models and the resilience of SMEs in Nigeria. This study offers helpful insights for SMEs looking to improve their business models and increase their sustainability in the face of shifting economic and environmental conditions by examining the connections between business model innovation, SMEs’ resilience, and technology.